Do We Really Know That the WTO Increases Trade? - Rose, Andrew K (American Economic Review, 2004)
This paper estimates the effect on international trade of multilateral trade agreements—the World Trade Organization (WTO), its predecessor the General Agreement on Tariffs and Trade (GATT), and the Generalized System of Preferences (GSP) extended from rich countries to developing countries. I use a standard “gravity” model of bilateral merchandise trade and a large panel data set covering over 50 years and 175 countries. An extensive search reveals little evidence that countries joining or belonging to the GATT/WTO have different trade patterns from outsiders, though the GSP seems to have a strong effect.